2022
DOI: 10.3389/fimmu.2022.891925
|View full text |Cite
|
Sign up to set email alerts
|

Responses of regulatory and effector T-cells to low-dose interleukin-2 differ depending on the immune environment after allogeneic stem cell transplantation

Abstract: CD4+Foxp3+ regulatory T cells (Tregs) play a central role in the maintenance of immune tolerance after allogeneic hematopoietic stem cell transplantation (HSCT). Tregs promptly respond to low concentrations of IL-2 through the constitutive expression of high-affinity IL-2 receptors. It has been reported that low-dose IL-2 therapy increased circulating Tregs and improved clinical symptoms of chronic GVHD. Clinical studies of IL-2 therapy so far have mainly targeted patients in the chronic phase of transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Using a mouse model, Meguri et al. ( 54 ) have shown that IL-2 therapy affects Treg and effector T cells (Teff) responses differently depending on the immune environment in the host. In mild inflammatory conditions, the IL-2 therapy controlled GVHD without affecting GVL.…”
Section: Enhancing the Gvl Effect After Treg Infusion For Gvhd Suppre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a mouse model, Meguri et al. ( 54 ) have shown that IL-2 therapy affects Treg and effector T cells (Teff) responses differently depending on the immune environment in the host. In mild inflammatory conditions, the IL-2 therapy controlled GVHD without affecting GVL.…”
Section: Enhancing the Gvl Effect After Treg Infusion For Gvhd Suppre...mentioning
confidence: 99%
“…In mild inflammatory conditions, the IL-2 therapy controlled GVHD without affecting GVL. Moreover, their results indicate that in an immune-tolerant state after HSCT, IL-2 therapy may even enhance the GVL effect without exacerbating GVHD ( 54 ). More recently, adaptations to the previous approaches using IL-2 therapy have been performed aiming to specifically promote Treg expansion and not alloreactive effector T cells.…”
Section: Enhancing the Gvl Effect After Treg Infusion For Gvhd Suppre...mentioning
confidence: 99%
“…In a clinical trial assessing the efficacy of low IL-2 to suppress allospecific immune responses and allow the complete discontinuation of maintenance immunosuppression in liver transplant recipients, rejection episodes were reported for four of five participants who initiated immunosuppression withdrawal [214]. Interestingly, exogenous IL-2, even at low doses, has been shown to induce conflicting effects on Tregs in the allo-HCT setting depending on the immune environment of the host; in a mild inflammatory state, low IL-2 regulated Treg homeostasis and suppressed GvHD, whereas in an intense inflammatory environment, the same IL-2 doses enhanced activated T cells rather than Tregs and exacerbated GvHD in a mouse model [217].…”
Section: Improving Treg Survival and Persistencementioning
confidence: 99%
“…Tregs, as discussed earlier. In fact, when IL-2 was combined with donor-specific Tregs, but not with polyclonal Tregs, it preferentially enhanced the proliferation of the allospecific Tregs and a synergistic effect in prolonging skin allograft survival was observed [217]. Nevertheless, IL-2 receptor complexes are also expressed on immune cells other than CD4+ T cells, making them responsive to IL-2.…”
Section: Improving Treg Survival and Persistencementioning
confidence: 99%
“…This type of micelle is well known for its capacity to entrap and deliver a broad range of hydrophobic drugs [31,32]. A large body of literature addressing DSPE-PEG2000 micelle use in drug delivery exists [33][34][35][36][37]. Properties like a low critical micellar concentration and aggregation number, good stability, a lean preparation process and affordability make DSPE-PEG2000 micelles a potentially good delivery platform even for RAD001.…”
Section: Introductionmentioning
confidence: 99%